MZC gel inhibits SHIV-RT and HSV-2 in macaque vaginal mucosa and SHIV-RT in rectal mucosa - Calenda, Giulia (J Acquir Immune Defic Syndr, 2017)
The Population Council’s microbicide gel MZC (also known as PC-1005) containing MIV-150 and zinc acetate dihydrate (ZA) in carrageenan (CG) has shown promise as a broad spectrum microbicide against HIV, HSV and HPV. Previous data show antiviral activity against these viruses in cell-based assays, prevention of vaginal and rectal SHIV-RT infection and reduction of vaginal HSV shedding in rhesus macaques and also excellent antiviral activity against HSV and HPV in murine models. Recently we demonstrated that MZC is safe and effective against SHIV-RT in macaque vaginal explants. Here we established models of ex vivo SHIV-RT/HSV-2 co-infection of vaginal mucosa and SHIV-RT infection of rectal mucosa in macaques (challenge of rectal mucosa with HSV-2 did not result in reproducible tissue infection), evaluated antiviral activity of MZC and compared qPCR and ELISA readouts for monitoring SHIV-RT infection. MZC (at non-toxic dilutions) significantly inhibited SHIV-RT in vaginal and rectal mucosa and HSV-2 in vaginal mucosa when present during viral challenge. Analysis of SHIV-RT infection and MZC activity by one-step SIV gag qRT-PCR and p27 ELISA demonstrated similar virus growth dynamics and MZC activity by both methods and higher sensitivity of qRT-PCR. Our data provide more evidence that MZC is a promising dual compartment multipurpose prevention technology candidate.